Islamic faith as a facilitator for accessing counselling: the experience of three Kuwaiti clients. Issue 6 (1st November 2020) - Al-Dousari, Mounira; Prior, Seamus
ABSTRACT: This paper draws upon qualitative research with three Kuwaiti counselling clients to explore how they negotiated accessing counselling in the context of their communities, culture and faith. Contrary to the prevailing view in the literature portraying Islamic faith as a barrier to help-seeking in mental health, these clients view their faith as an important facilitator for accessing formal help. In particular, participants distinguished faith from culture and appealed to sacred scriptures to demonstrate the convergence of Muslim values with help-seeking in relation to psychological distress. This paper offers an original and timely discussion of one aspect of the potential interface of Islamic faith and counselling, while acknowledging the limitations of the small self-selected sample from which the findings are drawn.